Corrosion Performance of Fe-Cr-Ni Alloys in Artificial Saliva and Mouthwash Solution - J. Porcayo-Calderon; M. Casales-Diaz; V. M. Salinas-Bravo; L. Martinez-Gomez (Bioinorganic Chemistry and Applications)
Several austenitic stainless steels suitable for high temperature applications because of their high corrosion resistance and excellent mechanical properties were investigated as biomaterials for dental use. The steels were evaluated by electrochemical techniques such as potentiodynamic polarization curves, cyclic polarization curves, measurements of open circuit potential, and linear polarization resistance. The performance of steels was evaluated in two types of environments: artificial saliva and mouthwash solution at 37°C for 48 hours. In order to compare the behavior of steels, titanium a material commonly used in dental applications was also tested in the same conditions. Results show that tested steels have characteristics that may make them attractive as biomaterials for dental applications. Contents of Cr, Ni, and other minor alloying elements (Mo, Ti, and Nb) determine the performance of stainless steels. In artificial saliva steels show a corrosion rate of the same order of magnitude as titanium and in mouthwash have greater corrosion resistance than titanium.